2017
DOI: 10.1002/qua.25460
|View full text |Cite
|
Sign up to set email alerts
|

Quantum chemical electron impact mass spectrum prediction for de novo structure elucidation: Assessment against experimental reference data and comparison to competitive fragmentation modeling

Abstract: We investigate the success of the quantum chemical electron impact mass spectrum (QCEIMS) method in predicting the electron impact mass spectra of a diverse test set of 61 small molecules selected to be representative of common fragmentations and reactions in electron impact mass spectra. Comparison with experimental spectra is performed using the standard matching algorithms, and the relative ranking position of the actual molecule matching the spectra within the NIST-11 library is examined. We find that the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
36
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(39 citation statements)
references
References 35 publications
3
36
0
Order By: Relevance
“…The accuracy of in silico generated peaks and their abundances have to be largely improved. A comparison between QCEIMS and CFM-ID has shown that both algorithms perform well enough to get correct identifications for half of the 61 investigated molecules [ 75 ]. However, certain rearrangement reactions, including McLafferty rearrangements, remain underestimated.…”
Section: In Silico Generation Of Mass Spectra and Ms/ms Spectramentioning
confidence: 99%
“…The accuracy of in silico generated peaks and their abundances have to be largely improved. A comparison between QCEIMS and CFM-ID has shown that both algorithms perform well enough to get correct identifications for half of the 61 investigated molecules [ 75 ]. However, certain rearrangement reactions, including McLafferty rearrangements, remain underestimated.…”
Section: In Silico Generation Of Mass Spectra and Ms/ms Spectramentioning
confidence: 99%
“…Similar to the evaluation of machine-learning prediction methods such as CFM-ID, 325 quantum chemical models have to be rigorously tested by comparing theoretical predictions against experimental reference spectra. 326 Similarity match scores and compound rankings should be reported. 294 This can be done with the National Institute of Standards and Technology (NIST) MS Search program and the NIST and MassBank of North America (MoNA) mass spectral databases.…”
Section: Current Applications and Real Examplesmentioning
confidence: 99%
“…The statistics of many fragmentation trajectories are then summarized to yield a list of fragment ions and their associated intensities [24]. While much theoretical work on QCEIMS has been published in the past [27][28][29][30][31][32][33][34], currently only four purines and pyrimidines have been investigated in detail [27]. Density function theory (DFT) has also been used for calculating the partition coefficients in organic solvents [35].…”
Section: Introductionmentioning
confidence: 99%